Pengaruh Pendidikan, Motivasi, dan Media Sosial terhadap Minat Kewirausahaan melalui Efikasi Diri : Studi pada Siswa Jurusan Agribisnis Pengolahan Hasil Pertanian (APHP) SMK Negeri 1 Jepara - Kusmuriyanto; Niswah Himmatul (Journal of Accounting, Economics, and Business Education, 2025)
High unemployment and limited job opportunities are complex problems. Based on Law Number 20 of 2003, SMK graduates are directed to become skilled workers, but limited employment opportunities are an obstacle. This study analyzes the effect of Entrepreneurship Education, Entrepreneurial Motivation, and Social Media Utilization on Entrepreneurial Interest through Self-Efficacy in Agricultural Product Processing Agribusiness students of SMK Negeri 1 Jepara. The population was 318 students with a sample of 177 students in grades X to XII selected using proportional random sampling method. Data analysis used descriptive statistics and path model regression with IBM SPSS 25. The results showed that entrepreneurship education, entrepreneurial motivation, and self-efficacy had a significant positive effect on entrepreneurial interest, while social media utilization had a significant negative effect. Self-efficacy has partially mediated the effect of motivation on entrepreneurial interest and full mediated social media utilization on entrepreneurial interest, but does not mediate the effect of entrepreneurship education on entrepreneurial interest. Simultaneously, the four variables explain 78.6% of the variation in entrepreneurial interest, while the rest is influenced by other factors. Students should be more active in entrepreneurial activities, schools emphasize technology-based entrepreneurship learning, and further research explore other factors that influence entrepreneurial interest.